Functional Diversity of CYCLOIDEA‐like TCP Genes in the Control of Zygomorphic Flower Development in Lotus japonicus. Issue 3 (9th January 2013) - Xu, Shilei; Luo, Yonghai; Cai, Zhigang; Cao, Xiangling; Hu, Xiaohe; Yang, Jun; Luo, Da
Abstract: CYCLOIDEA ( CYC )‐like TCP genes play key roles in dorsoventral differentiation of zygomorphic flowers in Papilionoideae legumes. In this study, we analyzed the kew mutants whose flowers lost lateral identity, and investigated the diverse functions of three LjCYC genes during zygomorphic flower development in the model legume Lotus japonicus . We showed that kew1 and kew3 are allelic mutants of LjCYC3, a CYC‐ like TCP gene. Through transgenic experiments, it was shown that LjCYC1 possesses dorsal activity similar to LjCYC2, and that LjCYC3 alone is sufficient to confer lateral activity, and an epistatic effect between dorsal and lateral activities was identified. Sequence analysis revealed a striking alteration at the 3′ end of the LjCYC3 open reading frame (ORF) in comparison with those of LjCYC1 and LjCYC2 ORFs. Furthermore, it was found that LjCYC proteins could interact with each other and possess different activities by means of a transcriptional activity assay. Our data demonstrate that the sequence variation and the subsequent alteration of protein property play important roles in the functional diversity of different LjCYC genes in controlling zygomorphic flower development in Lotus japonicus .